Spontaneous Blinking in Patients With Graves' Upper Eyelid Retraction - Garcia, Denny Marcos; Messias, Andre; Costa, Luciana Oliveira; Pinto, Carolina Trindade; Barbosa, Jose Carlos [UNESP]; Velasco Cruz, Antonio Augusto (Taylor & Francis Inc, 2010)
Purpose: To describe spontaneous blink kinematics in Graves' upper eyelid retraction (UER).Methods: The magnetic search coil technique was used to record spontaneous blinks of 15 healthy subjects (aged 23-56 years, 15 eyelids) and 15 patients with Graves' UER (aged 22-62 years, 15 eyelids) during a 5-min period of video observation, and the signals were digitized at 200 Hz (12 bits). Overall, a total of 2,798 blinks were recorded for the controls and 1,860 for the patients. The distance between pupil center and upper eyelid margin in the primary position of gaze (MRD) was measured with the Image J software.Results: The blinking rate of patients was lower than that of control subjects, with a mean (+/-SEM) blinking rate (blinks/min) of 13.0 +/- 1.7 for patients and of 20.0 +/- 2.1 for the controls (t = 2.58, P = 0.016). There were no statistically significant differences in blink amplitude between controls (22.7 +/- 3.1 degrees) and Graves' patients (24.7 +/- 3.3 degrees). However, while only 22% of the blinks performed by controls were smaller than MRD, this rate was 78% for patients. In addition, in blinks larger than 25, patients showed lower down-phase velocity than controls.Conclusions: Patients with Graves' UER show reduced blinks rates and abnormal blink kinematics, which might be related to the development of exposure keratitis in this disease.
Keywords: Blinking; Graves' orbitopathy; Eyelid retraction; Magnetic search coil; Blink kinematics